Is vanadium a more versatile target in the activity of primordial life forms than hitherto anticipated? - Rehder, Dieter (Organic & biomolecular chemistry, 2008)
The two predominant forms of vanadium occurring in the geo-, aqua- and biosphere, soluble vanadate(V) and insoluble oxovanadium(IV) (vanadyl), are subject to bacterial activity and transformation. Bacteria belonging to genera such as Shewanella, Pseudomonas and Geobacter can use vanadate as a primary electron acceptor in dissimilation or respiration, an important issue in the context of biomineralisation and soil detoxification. Azotobacter, which can employ vanadium as an essential element in nitrogen fixation, secretes a vanadophore which enables the uptake of vanadium(V). Siderophores secreted by other bacteria competitively (to ferric iron) take up vanadyl and thus interfere with iron supply, resulting in bacteriostasis. The halo-alkaliphilic Thioalkalivibrio nitratireducens possibly uses vanadium as a constituent of an alternative, molybdopterin-free nitrate reductase. Marine macro-algae can generate a variety of halogenated organic compounds by use of vanadate-dependent haloperoxidases, and a molecular vanadium compound, amavadin, from Amanita mushrooms has turned out to be an efficient catalyst in oxidation reactions. The present account is a focused and critical review of the current knowledge of the interplay of bacteria and other primitive forms of life (cyanobacteria, algae, fungi and lichens) with vanadium, with the aim to provide perspectives for applications and further investigations.